(3eQGJY GdZRdGf aj hUa GdMSGf ef GdZdeGfs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi Ndb GdEfSGf ai CMSf Jbhje abO SCdfi HYV GdENhGf Cf CLeY dg fHPg ai GdMSGf ef GdZdeGf , JRghG HfXe LhgQgG GdaQjO Ydi GdfMhQ SejJgG eQGJY GdZRdGf s
(3BNQgG (B:s
(3dh de Gcf QhVI ddMSf Ch adckG eG cGf LeY ajc GdZUf hGdbeQ dcGf CHdZ ai GdeYfi Je eQGJY GdZRdGf ai hUa GdMSGf ef GdZdeGf hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1650s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3MGdI GdfSNI LjOI s
Keywords: (3GdSjGSI hGdGLJeGYs